2022
DOI: 10.1093/ecco-jcc/jjac049
|View full text |Cite
|
Sign up to set email alerts
|

IL10 Secretion Endows Intestinal Human iNKT Cells with Regulatory Functions Towards Pathogenic T Lymphocytes

Abstract: Background and aims Invariant Natural Killer T (iNKT) cells perform pleiotropic functions in different tissues by secreting a vast array of pro-inflammatory and cytotoxic molecules. However, the presence and function of human intestinal iNKT cells capable to secrete immunomodulatory molecules such as IL-10 has never been reported so far. Here we describe for the first time the presence of IL10-producing iNKT cells (NKT10 cells) in the intestinal lamina propria of healthy individuals and of Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 67 publications
1
16
0
Order By: Relevance
“…Alternatively, if human iNKT cells generally retain functional plasticity, it may be important to identify methods to specifically promote their regulatory functions. To this end, a recent study found that the presence of IL-7 during in vitro expansion of human iNKT cells resulted in a CD4 + population with enhanced T H2 cytokine production ( 106 ), while exposure to short chain fatty acids, palmitate, or the mTOR inhibitor rapamycin may induce a regulatory phenotype ( 27 , 37 , 107 ). Another important consideration is that iNKT immunotherapy that engages T H2 pathways would likely be contraindicated in certain inflammatory diseases, including asthma, chronic obstructive pulmonary disease, and ulcerative colitis, where T H2 cytokine production by iNKT cells has been associated with disease-exacerbating effects (reviewed in ( 108 110 )).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, if human iNKT cells generally retain functional plasticity, it may be important to identify methods to specifically promote their regulatory functions. To this end, a recent study found that the presence of IL-7 during in vitro expansion of human iNKT cells resulted in a CD4 + population with enhanced T H2 cytokine production ( 106 ), while exposure to short chain fatty acids, palmitate, or the mTOR inhibitor rapamycin may induce a regulatory phenotype ( 27 , 37 , 107 ). Another important consideration is that iNKT immunotherapy that engages T H2 pathways would likely be contraindicated in certain inflammatory diseases, including asthma, chronic obstructive pulmonary disease, and ulcerative colitis, where T H2 cytokine production by iNKT cells has been associated with disease-exacerbating effects (reviewed in ( 108 110 )).…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of human iNKT cells have suggested that they may participate in similar regulatory processes. IL-10 producing iNKT cells recently identified in the intestinal lamina propria of Crohn’s Disease patients showed suppressive activity towards pathogenic CD4 + T cells, and the frequency of IL-10 producing iNKT cells in colon tissue of these patients correlated inversely with T H1 and T H17 cell frequency, and was associated with reduced disease severity, higher TGFB gene expression, and lower levels of inflammatory proteins ( 37 ). Moreover, co-culture of human T regs with iNKT cells led to increased T reg FOXP3 expression, enhanced IL-10 secretion, and more profound inhibition of conventional T cell proliferation ( 38 ).…”
Section: How Are the Anti-inflammatory Effects Of Inkt Cells Mediated?mentioning
confidence: 99%
“…Single-cell suspensions were prepared from the colon of C57BL/6, Traj18 -/- and CD1d -/- mice as previously described 9 . Briefly, cells were isolated via incubation with 5 mM EDTA at 37°C for 30 min, followed by mechanical disruption with GentleMACS (Miltenyi Biotec).…”
Section: Methodsmentioning
confidence: 99%
“…Intestinal mucus scraped from the human and murine colons were stored at -80°C until DNA extraction. DNA extraction, 16S rRNA gene amplification, purification, library preparation and pair-end sequencing on the Illumina MiSeq platform were performed as previously described 9 . Reads were pre-processed using the MICCA pipeline (v.1.7.0) (http://www.micca.org) 48 as previously described 9 .…”
Section: S Rrna Gene Sequencing and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation